Methodological provision of th analysis and assessment of the development of the circular economy in the EU - Оleksandr Shubalyi; Viktor Khomytskyi; Svitlana Moshchych (Економічний форум)
The article examines the peculiarities of methodological support for the analysis and assessment of the development of the circular economy in the EU countries, which was developed by Eurostat. The main purpose of the article is to study methodological approaches and the results of their use for the analysis and assessment of the development of the circular economy in the countries of the European Union from the standpoint of the possibility of their further use in statistical practice in Ukraine to accelerate the process of European integration. The urgency of solving this scientific problem lies in the fact that it is very important for Ukraine to speed up the process of harmonizing the domestic institutional environment to EU standards. The study of the Eurostat methodology for the analysis and assessment of the development of the circular economy, which contains 10 key indicators, which are divided into four groups and cover the following areas: production and consumption, waste management, secondary raw materials, competitiveness and innovation, became the methodological tool of the research. The main indicators of monitoring and evaluation include: the Sankey diagram of material flows in EU countries, as well as the circulation coefficient of materials that are processed and returned to the economy. The object of the study is the methodical approaches used by Eurostat to analyze and evaluate the development of the circular economy. The article examines Eurostat's experience in using the Sankey diagram visualization tool and its analysis according to various criteria, in particular, according to the main types of material flows (biomass, metal ores, non-metallic minerals, fossil carriers/energy materials), which significantly expands the capabilities of analytics and effective decision-making in this field. It was concluded that it is important for Ukraine to adapt and harmonize domestic statistics in accordance with the methodical approaches defined by Eurostat, highlighting a separate direction - circular economy development statistics. The results of the study can be useful for the state statistics authorities in Ukraine to adapt the methodological approaches adopted in the EU countries for the analysis and assessment of the development of the circular economy, as well as the state authorities for the implementation in the domestic institutional environment of European principles, concepts and normative acts to stimulate the transition to sustainable growth and development of the circular economy, which will contribute to the acceleration of the process of gaining full membership of Ukraine in the European Union